Lumbar interbody expanding cage - Manunta, M. L.; Careddu, G. M.; Masala, G.; Columbano, N.; Doria, C.; Crissantu, L.; Sanna Passino, E. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Interbody fusion devices are used in human medicine for treating degenerative diseases of the spine. Currently, there is not a universally accepted assessment tool for determining fusion, and the definitive criteria for diagnosing a successful interbody fusion remain controversial. The aim of this study was to describe microscopic and helical computed tomography (CT) imaging in the assessment of lumbar interbody fusion using cylindrical threaded titanium expanding cage in sheep. One cylindrical threaded expanding titanium cage (Proconcept – SA, Orange, France) was inserted through a transperitoneal approach after radical discectomy and packed with cancellous bone autograft in five adult sheep. The subjects were euthanatized after three, six, 12, 18 and 24 months. CT images revealed lumbar fusion at 12 months post operation, whereas microscopic evaluations indicated the presence of lumbar fusion at 18 months. CT and histological grades were the same in 65% of the cases observed. There were not a significant difference between CT, histological and micro radiographic grades. Helical CT scanning can be considered to be a suitable method for the monitoring of lumbar fusion as it enables observation of the deposition of bony bridging within the cage.
Keywords: Threaded expanding cage; lumbar spine; vertebral fusion; arthrodesis; animal model